La estimulación temprana y su incidencia en el desarrollo cognitivo de los niños y niñas de educación inicial dos del centro de desarrollo infantil Perpetuo Socorro de la ciudad de Quito, período lectivo 2013-2014 - Portilla Montenegro, Olga Yolanda (2015)
This research refers to "EARLY STIMULATION AND ITS IMPACT ON THE COGNITIVE DEVELOPMENT OF CHILDREN OF PRESCHOOL EDUCATION II CHILD DEVELOPMENT CENTER" PERPETUO SOCORRO" FROM QUITO, LECTIVO PERIOD 2013-2014" it was structured and developed as established by the National University of Loja. From disclose through research the importance of early stimulation on cognitive development of children in early education II Child Development Center: Similarly a general objective was formulated. In the scientific methodology, Deductive, Inductive, Analytical and Statistical Model that served them helps to achieve the proposed goal effectively used method; techniques used were: A survey of early education teachers Il, the Child Development Center "Perpetual Help" from the city of Quito, to determine early stimulation in the daily work and the Cognitive test that applied to children early education II, to determine the Cognitive Development. To which reference was made to question # 1 you think. That early stimulation directly influences within the teaching-learning process? reflects a 100% result in the teachers state that influences whether early stimulation in the teaching-learning process as it helps awaken mental processes in the brain of children. In the survey of parents was taken as reference question # 1 Do you think that early stimulation your child receives / a CDI influences on Cognitive Development? reflects a 84% result in which parents report that if it receives stimulation influences represented in the CDI for Cognitive Development because, as it helps to potentiate their full potential in all areas. According to the results of the Cognitive test is concluded that: 54% of boys and girls surveyed obtained a level of Excellent Cognitive Development; means 40% and 6% lower, so that the master can determine that mostly been made good work with students in cognitive development, but must continue in order to reach all level of excellence.